Financial literacy, fintech adoption, and school financial management effectiveness: a mediation analysis - Yulianto Santoso; Widiawati Widiawati (Indonesian Institute for Counseling, Education and Therapy (IICET), 2026)
As the implementation of digital financial systems in schools becomes increasingly widespread, understanding the various factors that can enhance the effectiveness of financial management becomes highly crucial. This study aims to examine the effect of financial literacy on the effectiveness of school financial management, with the implementation of FinTech serving as an mediating variable. The study employed a census design involving all 117 public vocational high school principals in West Sumatra Province (100% response rate). Data were collected using a structured questionnaire consisting of 18 items measured on a five point Likert scale assessing financial literacy, FinTech adoption, and financial management effectiveness. The hypotheses were tested using PLS-SEM with the support of SmartPLS 4.0 software. Financial literacy significantly influences the effectiveness of school financial management (β = 0.581, p < 0.000) and also has a significant indirect effect through FinTech adoption (β = 0.195, p < 0.000), indicating partial mediation. These findings highlight the importance of enhancing FinTech and adopting FinTech to sustainably improve the effectiveness of financial management. The findings demonstrate that FinTech adoption partially mediates the relationship between financial literacy and financial management effectiveness, highlighting the strategic role of digital financial integration in strengthening school governance.